2017
DOI: 10.1016/j.ophtha.2016.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the Palpebral Conjunctiva

Abstract: A comparative study of the effect of fibrin glue versus sutures on clinical outcome in patients undergoing pterygium excision and conjunctival autografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…7 Conjunctival leiomyomas have also been reported to arise from the palpebral and epibulbar conjunctiva. 8–10 Leiomyosarcoma, a malignant smooth muscle tumor, should also be considered in the differential diagnosis. Thirteen cases of this tumor have been previously reported on the conjunctiva.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Conjunctival leiomyomas have also been reported to arise from the palpebral and epibulbar conjunctiva. 8–10 Leiomyosarcoma, a malignant smooth muscle tumor, should also be considered in the differential diagnosis. Thirteen cases of this tumor have been previously reported on the conjunctiva.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A leiomyoma is another benign lesion that has previously been described as a nodule on the lower eyelid, composed of intersecting fascicles of spindle-shaped cells. 7 Conjunctival leiomyomas have also been reported to arise from the palpebral and epibulbar [8][9][10] Leiomyosarcoma, a malignant smooth muscle tumor, should also be considered in the differential diagnosis. Thirteen cases of this tumor have been previously reported on the conjunctiva.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Its location has been described intraorbital in 25 cases; histological characteristics and the absence of recurrence after complete resection support their benign behavior 6. On the other hand, Lin J, et al 7 reported eight cases of angioleiomyoma, of which six were intraconal and two were located in the eyelid, and were more frequent in males. The palpebral conjunctiva is another uncommon site where leiomyoma has been reported 8 .…”
Section: Introductionmentioning
confidence: 99%
“…reportaron ocho casos de angioleiomioma, de los cuales seis ocurrieron intraconales y dos a nivel palpebral, y fueron más frecuentes en el sexo masculino. La conjuntiva palpebral es otro de los sitios poco comunes donde se ha reportado la presencia de leiomioma 8 .…”
Section: Introductionunclassified